ORAL CLEFTS - A CASE-CONTROL STUDY - Loffredo, LDM; Desouza, JMP; Yunes, J.; Freitas, JAD; Spiri, W. C. (Revista De Saude Publica, 1994)
This study relates to a case-control analysis for the purpose of verifying the association between oral clefts and possible risk factors. The analysed variables were: place of mother's residence (urban/rural), pollution, parental diseases, mother's diseases during the first four months of pregnancy, intake of drugs related to this period, heredity, smoking habits, alcohol consumption and X-ray examinations during pregnancy or X-ray examinations prior to pregnancy. There were 450 cases of clefts of whom 354 had a cleft lip with or without cleft palate and 96 had a cleft palate. The relative risk (RR) for each variable by was estimated points and at a 95% of confidence interval and multivariate analysis was applied. As regards cleft lip with or without cleft palate, the risk factors are heredity (RR = 4.96), epilepsy in the mother (RR = 2.39) and the intake of drugs such as anti-inflammatory substance in the first four months of pregnancy (RR = 2.59). Related to cleft palate, the risk factors are heredity (RR = 2.82) and pollution (RR = 2.58).
Keywords: CLEFT LIP; EPIDEMIOLOGY; CLEFT PALATE; RISK FACTORS